Desconsideração da personalidade jurídica - Reis, Jessé Galhardo Ribeiro (2016)
This paper develops the study of the surrounding factors in the context of piercing the corporate veil, analyzing the facts, consequences and evolution of the legal system for that matter, and all the importance of the means adopted to guarantee all existing legal provisions. It brings the history of the system used in the legal sphere, analyzing the behavior of society and determines which the objectives and main characteristics of its creation to the effective application in today's media. Concepts trends and effects of the practice, exposing the real consequences and possible problems to be generated in the legal environment. Presents a study of standardization of Brazilian law according to the evolution that follows the company, the risks that the legal system may provide and the benefits derived from the collective and individual coming from a clear idea with legal certainty regarding asset separation between company and partner. Parallel between the right and the purpose of avoiding the use of assets improperly with the purpose of shielding and malicious conduct. Exposes points as issues of controversial issues in search of an improvement in the applicability of the ordinary issues of today's society, such as applicability and effects of which are not always in accordance with the casual reality. concluding to the evolution that is required of the science of law, in the manner in which they must evolve coming as close as possible to the assertiveness of an effective system, modern and safe, since it requires constant changes to accompany a modern society, current and increasingly under development